2006
DOI: 10.2965/jwet.2006.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urban emissions on the horizontal distribution of metal concentration in sediments in the vicinity of Asian large cities

Abstract: Abstract:Metal contents of sediments in Manila Bay -Laguna Lake watershed in the Philippines were measured and detailed horizontal distribution was obtained. The distribution of zinc and lead concentration in Manila Bay clearly shows the effect of anthropogenic contamination and it was explained by the diffusion of lead and zinc rich anthropogenic particles discharged from Pasig River. The sediments in Laguna Lake were mostly natural particulate matters from surrounding mountains and they contained 20 mgPb/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The heavy metal concentrations in the coastal sediments of the atoll were much lower than those in the coastal, estuarial, bay, river, lake and agricultural sediments in other environments (except coral reefs) (Hakanson, 1980;Tomlinson et al, 1980;Urase et al, 2006;Amin et al, 2009;Bhuiyan et al, 2010;Varol, 2011). The heavy metal contamination shows considerable variation in both the concentration and presence of different heavy metals.…”
Section: Avs and Heavy Metals In The Coastal Sedimentsmentioning
confidence: 91%
“…The heavy metal concentrations in the coastal sediments of the atoll were much lower than those in the coastal, estuarial, bay, river, lake and agricultural sediments in other environments (except coral reefs) (Hakanson, 1980;Tomlinson et al, 1980;Urase et al, 2006;Amin et al, 2009;Bhuiyan et al, 2010;Varol, 2011). The heavy metal contamination shows considerable variation in both the concentration and presence of different heavy metals.…”
Section: Avs and Heavy Metals In The Coastal Sedimentsmentioning
confidence: 91%
“…The river is now very polluted due to a human negligence and industrial development [1]. There are many research papers [2][3] focusing on the investigation of the river, however no study has made considerable progress from the point of view of purification. Previously, one author investigated the COD (chemical oxygen demand) at about 15 points along the river [2] and it is interesting to note that the recent COD measurement conducted in the river showed that the value has almost doubled since the year 2000.…”
Section: Purification Experiments On the Pasig River Philippines Using A Circulation-type Purification System 1 Introductionmentioning
confidence: 99%
“…In Southeast Asia, heavy metals are being accumulated in urban rivers, estuaries, and adjacent coastal zones (Prudente et al, 1994;Urase et al, 2006;Thongra-ar et al, 2008;Zhu et al, 2010) as one of the consequences of the recent rapid urbanization and industrialization. Bioavailability and toxicity of heavy metal depend on its concentration as well as chemical speciation.…”
Section: Introductionmentioning
confidence: 99%
“…Such high sediment load is largely the result of natural processes (e.g., erosion and transport) in their catchments and often makes water quality control complex in terms of water supply as well as ecological management. Consequently, the deterioration of aquatic ecosystems is closely related to SS in highly turbid rivers because SS serves as the carrier of a number of pollutants including heavy metals, causing secondary and tertiary pollutions in adjacent water bodies (Urase et al, 2006;Zhu et al, 2010), and SS can be also potential food sources for aquatic fauna.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation